(untitled) - Headland, Isaac Taylor (New York, 1909)
For twenty years and more Mrs. headland has been physician to the family of the Empress Dowager's mother, the Empress' sister, and many of the princesses and high offical ladies in Peking. She has visited them in a social as well as a professional way, has taken with her her friends, to whom the princesses have shown many favours, and they have themselves been constant callers at our home.